Differences in Motor Abilities of Younger School Children based on their Sex - Miroslav Smajic; Ana Ivanov; Nebojsa Cokorilo; Goran Dimitric; Valdemar Stajer; Bogdan Tomic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The aim of this research is to determine whether there is any statistically signifi cant diff erence in motor abilities of boys and girls of younger school age. The sample includes 76 examinees with 37 males and 39 females. All are 5th and 6 th graders of primary school. The evaluation of motor abilitied is based on 5 tests. Multivariant analysis of variance is applied for determination of diff erences within the whole system of motor tests, whereas univariant analysis of variance is used for determining diff erences in each motor test. According to the fi ndings, statistically signifi cant diff erences in motor abilities between boys and girls at the studied age can be noticed in the test 20 m running from fl ying start, which is in favour of boys and in the test sit and reach, in favour of girls, while the diff erences in other tests are not statistically signifi cant. Considering the evaluation of motor abilities, boys have statistically much better results in the speed of alternative movements and explosive strenth, whereas girls have achieved much better results in the test for fl exibility. It has also been concluded that 5th and 6th graders have statistically better results in the space of coordination and explosive strenght, whereas girls are much better in the fi eld of fl exibility and suppleness.